Recycling and Characterization of Metallic Chips Using Powder Metallurgy - DEMİREL, Handan and GÜNEŞ , Aydın and ŞAHİN, Ömer Sinan (International Journal of Computational and Experimental Science and Engineering, 2019)
In this study, a new metal matrix composite material was produced by sintering from cast iron and bronze shavings made by recycling melting method. In the production of metal matrix composite material, 90% CuSn10 as a matrix material and 10% GGG40 cast iron as a reinforcement material were used. The chips having the same dimensions were mixed in a homogeneous mixture and pre-formed under a pressure of 1146 MPa and then sintered at 875 °C. The mechanical properties and porosity of the produced materials are characterized and the mechanical properties are compared with the mechanical properties of the bronze material in bulk state. According to the results, the mechanical properties of the material produced by the sintering method are very close to that of the bronze material in the bulk state.